Impact of the COVID-19 pandemic on orthopaedic and traumatological care in Prague, the capital of the Czech Republic - Fulin, Petr; Daniel, Matej; Walder, Jiri; Grzelecki, Dariusz; Pokorny, David (PLoS One, 2022)
The coronavirus disease (COVID-19) has significantly affected society, especially healthcare systems worldwide. The aim of this retrospective study is to evaluate the impact of the COVID-19 pandemic on orthopaedic and trauma healthcare at the largest university hospital in the Czech Republic. The evaluated periods were in accordance with three waves of the disease and three respective lockdowns. To correlate the results, we evaluated the number of patients (inpatients and outpatients) treated in the same period in the last 3 years before the pandemic. The number of orthopaedic outpatients during the lockdown period decreased by 54.12% (p = 0.002), 42.88% (p <0.001), and 34.53% (p = 0.03) in the first, second, and third lockdowns, respectively. The number of elective surgeries decreased by 69.01% (p <0.001), 87.57% (p <0.001), and 74.89% (p = 0.007) and the number of acute surgeries decreased by 33.15% (p = 0.002), 37.46% (p <0.001), and 27.24% (p = 0.034) in the first, second, and third lockdowns, respectively. This study showed a significant reduction in the healthcare of orthopaedic and trauma patients owing to the COVID-19 pandemic and emphasised the shortcomings of the healthcare system. In our study, there was a reduction in both outpatient (reduction of care by 24-54%) and inpatient care. The elective surgeries were reduced by 69-87% during different lockdown periods compared with the reference period. Based on the results of this study, we can formulate organisational measures to mitigate the impact of the pandemic on orthopaedic healthcare. Organisational procedures created based on acquired data and experience should maximise the bed capacity of the workplace and work efficiency with regard to the safety of medical staff.
Keywords: ortopedie; pandemie; Czech Republic; COVID-19; lidé; SARS-CoV-2; Pandemics; retrospektivní studie; Humans; Orthopedics; Retrospective Studies; kontrola infekčních nemocí; Česká republika; Communicable Disease Control